THE EFFECT OF SOCIAL MEDIA INSTAGRAM ON SUNDA CHARACTER DEGRADATION IN HIGH SCHOOL STUDENTS IN BANDUNG CITY. (Descriptive Study of High School Students in Bandung City) - Mohammad Rizal, - (2019)
Instagram social media is one of the most popular social media in the world, in Indonesia Instagram social media itself has many users from various circles, this is caused by the image sharing feature that is owned by social media Instagram, its use is quite easy for everyone, but the media Social Instagram has a negative impact on its users, especially among high school students. This article focuses on, the use of Instagram social media among high school students, the form of degradation in the values of Sundanese characters caused by Instagram social media, and how much influence Instagram social media has on the degradation of Sundanese character values. The values of the Sundanese Character in this study focused on Lima Pinunjul, Sirna Ning Hurip and Sirna Ning Hirup. The values of the Sundanese Character aim to regulate the behavior of the Sundanese people. The method used in this study is descriptive with a quantitative approach, with the technique of collecting data using a closed questionnaire. The population and sample in this study involved 116 students who had Instagram social media accounts spread across four high schools in the city of Bandung. School sampling is done randomly. The results showed that Instagram social media had an influence on student behavior in carrying out their daily activities, and Instagram social media indirectly shifted the values of Sundanese characters among high school students in the city of Bandung.; Media sosial Instagram adalah salah satu media sosial terpopuler di dunia, di Indonesia sendiri media sosial Instagram memiliki banyak pengguna dari berbagai kalangan, hal ini diakibatkan oleh fitur berbagi gambar yang dimiliki oleh media sosial Instagram, penggunaannya pun tergolong cukup mudah bagi semua orang, tetapi media sosial Instagram memiliki dampak negatif terhadap penggunanya, khususnya di kalangan siswa SMA. Artikel ini berfokus kepada, bentuk penggunaan media sosial Instagram di kalangan siswa SMA, bentuk dari degradasi nilai-nilai karakter Sunda yang diakibatkan oleh media sosial Instagram, dan seberapa besar pengaruh media sosial Instagram terhadap degradasi nilai-nilai karakter Sunda. Nilai-nilai Karakter Sunda dalam penelitian ini berfokus kepada Lima Pinunjul, Sirna Ning Hurip dan Sirna Ning Hirup. Nilai-nilai Karakter Sunda tersebut bertujuan untuk mengatur tingkah laku masyarakat Sunda. Metode yang digunakan dalam penelitian ini adalah deskriptif dengan pendekatan kuantitatif, dengan teknik pengumpulan data menggunakan angket tertutup. Populasi dan sampel dalam penelitian ini melibatkan 116 siswa yang mempunyai akun media sosial Instagram yang tersebar di empat SMA di Kota Bandung. Pengambilan sampel sekolah dilakukan secara acak. Hasil penelitian menunjukkan bahwa media sosial Instagram memiliki pengaruh terhadap perilaku siswa dalam menjalankan aktivitasnya sehari-hari, dan media sosial Instagram secara tidak langsung menggeser nilai-nilai karakter Sunda di kalangan siswa SMA di Kota Bandung.